Compact L-band switchable dual wavelength SOA based on linear cavity fiber laser - Ahmad, Harith; Zainudin, F.M.; Azmi, Atiqah Nabieha; Thambiratnam, Kavintheran; Ismail, Mohammad Faizal; Aminah, Nanik Siti; Zulkifli, Mohd Zamani (Elsevier, 2019)
A semiconductor optical amplifier (SOA) based linear cavity L-band dual wavelength fiber laser (DWFL) with a switchable output is proposed and its operation demonstrated. The DWFL is configured as a linear cavity, with a 1 × 24 arrayed waveguide grating together with two optical switches providing channel spacing tunability. An L-band SOA, with a central operating wavelength of 1580 nm and an operation bandwidth of 1500–1640 nm serves as the gain medium of the proposed laser cavity. The DWFL is able to generate a dual-wavelength output, with the widest spacing obtained being 18.7 nm and the narrowest spacing being 0.8 nm. The generated output is highly stable, with only minor power fluctuations of less than 2 dB as well as having a signal-to-noise ratio of 42 dB. The proposed setup would have numerous uses, particularly for sensor applications.